IN MEMORIAM PROF. IR. KUSNOTO SETYODIWIRYO - Rifai, Mien A. (REINWARDTIA, 1982)
After a long illness, Prof. Ir. Kusnoto Setyodiwiryo died peacefully in his home in Bogor on 29 April 1981. He was the first Indonesian to become the Director of the Botanical Gardens of Indonesia, the forerunner of the National Biological Institute.